ChemInform Abstract: A Novel Inorganic Solid State Ion Conductor for Rechargeable Mg Batteries. Issue 13 (1st April 2014) - Higashi, Shougo; Miwa, Kazutoshi; Aoki, Masakazu; Takechi, Kensuke
Abstract Mg(BH4)(NH2) (I) is prepared by ball milling of a 1:1 molar mixture of Mg(BH4)2 (II) and Mg(NH2)2 followed by annealing.